2023
DOI: 10.1021/acssynbio.2c00568
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Gene Expression by a Genetic Circuit for Chemical Production in Escherichia coli

Abstract: Gene expression in spatiotemporal distribution improves the ability of cells to respond to changing environments. For microbial cell factories in artificial environments, reconstruction of the target compound's biosynthetic pathway in a new spatiotemporal dimension/scale promotes the production of chemicals. Here, a genetic circuit based on the Esa quorum sensing and lac operon was designed to achieve the dynamic temporal gene expression. Meanwhile, the pathway was regulated by an Lcysteine-specific sensor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The plasma membrane-anchoring strategy initially improved the titer of geraniol, this result suggested that reconstruction of the MVA pathway to a new spatial dimension could facilitate the synthesis of geraniol. However, the biomass of the plasma membrane-anchored strains was significantly lower compared to the control strain CgOYE2Δ (Figure A).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The plasma membrane-anchoring strategy initially improved the titer of geraniol, this result suggested that reconstruction of the MVA pathway to a new spatial dimension could facilitate the synthesis of geraniol. However, the biomass of the plasma membrane-anchored strains was significantly lower compared to the control strain CgOYE2Δ (Figure A).…”
Section: Resultsmentioning
confidence: 96%
“…8,9 Subcellular compartmentalization strategies, a key advantage of eukaryotes over prokaryotes, have been reported to improve protein expression 10 and have been successfully implemented to improve the production of highvalue-added compounds in a variety of organelles, such as mitochondria, 11 peroxisomes, 7,12 endoplasmic reticulum, and lipid droplets. 13,14 Recently, plasma membrane targeting strategies have been used to facilitate the production of valuable chemicals 15 and to address intrapathway competitions. 16 As well, some studies have improved the functional expression and substrate accessibility of membrane-anchored enzymes by relocalizing key rate-limiting enzyme genes to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In previous studies, elevating the expression of desensitized serine acetyltransferase (SAT) proved to be a successful strategy for increasing the yield of L-cysteine. [5,8] However, many regulatory mechanisms involved in L-cysteine biosynthesis remain unresolved. [9][10][11][12] One of the major issues is the cytotoxicity associated with L-cysteine.…”
mentioning
confidence: 99%